Prognostic value of index of cardiac electrophysiological balance among US middle-aged adults - Chen, Xiaolong; Wang, Zhe; Liu, Lin; Zhang, Wei; Tang, Zhiguo; Liu, Bo; Zhang, Xuejun; Wei, Na; Wang, Junkui; Liu, Fuqiang; Ma, Meijuan (Frontiers in Cardiovascular Medicine, 2023)
Background: Index of cardiac electrophysiological balance (iCEB) has been widely used in clinical practice but no studies investigated the association between iCEB and prognosis in the general population. Objective: To assess the correlation between the iCEB and the prognosis in the general population. Methods: This retrospective cohort study involved adults aged 40–65 years who participated in the Third National Health and Nutrition Examination Survey (NHANES-III) and whose electrocardiograms were in sinus rhythm. The corrected iCEB (iCEBc) was the ratio of corrected QT interval (QTc) to QRS duration, and outcomes were cardiac and all-cause mortality. Cox proportional hazards regression model was used to identify the associations of iCEBc with end point. The value of iCEBc for predicting adverse events was evaluated by reclassification and discrimination analyses. Results: Among 5010 participants (mean age 51.10±7.67 years, 52.5% female), 3454 (68.9%) were Non-Hispanic White. The mean iCEBc was 4.45±0.56. A total of 2147 deaths were recorded during a median follow-up of 319 months. The adjusted model shown iCEBc was an independent risk factor for all-cause death. The iCEBc was linearly correlated with all-cause mortality and the optimal cutoff value was 4.57 in males and 4.98 in females. In the resultant model, prolonged iCEBc remained independently associated with a higher rate of mortality (HR: 1.25; 95% CI: 1.11-1.42) and cardiac death (HR: 1.34; 95% CI: 1.04-1.71). Among the complete study population or the group with a normal QTc interval, the performance of the predictive model after addition of iCEBc was not weaker than the model after the addition of prolonged QTc. Conclusions: Elevated iCEBc (male ≥4.57 and female ≥4.98) is an independent risk factor for cardiac or all-cause death among the middle-age adults. The clinical application value of iCEBc is firmly based on basic physiological principles and its use warrants further attention.